Teachers’ Talk: Expectations and Challenges in Using the Hablo App in EFL Clasroom - Rahma Laila Tambunan; Deasy Yunita Siregar (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
The integration of digital technology in education has become a global phenomenon that is changing the paradigm of learning in the 21st century. In Indonesia, the adoption of mobile learning applications such as Hablo App shows an increasing trend in line with the national digital literacy agenda. Teachers, as the main implementers, face a dilemma between the transformative potential of technology and the reality of technical and pedagogical constraints in the field. This study used an exploratory qualitative case study design with a purposive sampling approach involving two teachers who had implemented the Hablo App. Data collection involved observation and interviews was administered to gather specific data about usage patterns, satisfaction levels, and technical difficulties. This study emphasizes the expectations and challenges of teachers regarding the use of the Hablo App in classroom. These findings hold significant implications for educational app developers, language educators, and policymakers aiming to optimize digital learning.